Study on mode I fracture toughness of rocks using flat-joint model and moment tensor. (August 2022) - Wu, Shunchuan; Sun, Wei; Xu, Xueliang
Highlights: The notch shape plays a considerable role on the micro-cracks, cracking mechanisms, post-failure behavior. The moment tensors suggests that the chevron notch is more likely to cause ideal mode I fracture. The fully-developed fracture process zone (FD-FPZ), nature of source and energy characteristic are associated with heterogeneity. Abstract: The semi-circular bend specimens with straight and chevron notches have been widely used to determine the fracture toughness owing to their simplicity and convenience of testing. The notch shape, model size and heterogeneity affect the cracking mechanism and the accuracy and feasibility of the mode I fracture toughness, which typically leads to deviations from different methods. In this paper, the flat-joint model is used to calibrate Kowloon granite with uniaxial compressive strength, indirect tensile strength, Young's modulus and mode I fracture toughness (semi-circular bend (SCB) test) of approximately 180 MPa, 5.6 MPa, 20 GPa and 1.24 MPa·m 0.5 . The moment tensor is used to quantitatively investigate fracture process of SCB and the cracked chevron notched semicircular bend (CCNSCB) specimens of Kowloon granite with a loading rate of 0.0084 m/s. During modelling, the failure model and microcracking mechanism are quantified and compared in detail against laboratory data in the literature. The results indicate that the chevron notch is more likely to cause ideal mode I fracture due to its higher proportion of tensile source and larger average value of k . Size effect analysis is used to verify the ISRM-suggested size for the SCB specimen and provide some size recommendations of the CCNSCB specimen. Three typical classification methods are used to quantitatively study the effect of heterogeneity on cracking mechanisms suggesting that for the fully-developed fracture process zone (FD-FPZ), the nature of the source and energy characteristics are associated with heterogeneity. These results shed some light on the microcracking mechanism of the SCB and CCNSCB tests.